IMPACT OF QUR’ANIC NARRATIVES IN SURAH AL-KAHF ON THE LIFE OF MUSLIMS IN NORTH-WEST, NIGERIA - Attahir Shehu Mainiyo (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
This article assesses the significance of the Qur’anic narratives among Muslims in North-West Nigeria and its relevance to religious, cultural and social lives. The Glorious Qur’an, considered as a Divine Book by Muslims holds a central position in the belief system of Muslims the world over, including North-West Nigeria. It serves as a comprehensive guide encompassing morality, personal conduct as well as social justice. The study explores how the Qur’anic narratives shape the religious and moral identity of Muslims in the region. It highlights the role of the Qur’an in influencing belief and practice and how it provides moral and ethical principles, social norms and spiritual guidance. It also emphasizes the impact of the Qur’anic narratives on the social and political landscape of the region. The need to rely on the Qur’an to address contemporary issues and provide guidance, justice and social cohesion was also addressed. Overall, the article underscores the profound influence of the Qur’anic narratives among Muslims in north-West Nigeria. By understanding the relevance of Qur’anic narratives, policymakers, researchers and stakeholders will better be informed of the useful insights into the dynamics of the Muslim population in North-West Nigeria and foster an inclusive and informed approach to engage with this all-important religious text. It is thus in line with this backdrop that this article intends to assess the impact of Qur’anic narratives on the lives of Muslims in north-West Nigeria. To achieve the objectives of the research, the article adopts analytical phenomenological methodology.